(untitled) (mathematica didactica, 2021)
An alternative approach to existing heuristic training programs has been developed using heuristic prompts as aid cards, so called strategy keys. The keys are presented to the students before working on a mathematical problem, are on the table during the entire process and can be used to overcome barriers during the solving process. In this explorative study we investigated how the use of strategy key influences the use of heuristics in problem solving process by primary school children. We found, that (1) in most cases the use of strategy keys results in a change or refinement of the strategy used before; (2) the quality of a strategy is changed due to the key usage and (3) students use the keys to name the used strategy. These activities can be interpreted as self-regulation. Thus, selfregulation can be stimulated when offering strategy keys.